Enhanced β‐phase in PVDF polymer nanocomposite and its application for nanogenerator. (28th June 2017) - Singh, Huidrom Hemojit; Singh, Simrjit; Khare, Neeraj
Abstract : Harvesting energy from the ambient mechanical energy by using flexible piezoelectric nanogenerator is a revolutionary step toward achieving reliable and green energy source. Polyvinylidene fluoride (PVDF), a flexible polymer, can be a potential candidate for the nanogenerator if its piezoelectric property can be enhanced. In the present work, we have shown that the polar crystalline β ‐phase of PVDF, which is responsible for the piezoelectric property, can be enhanced from 48.2% to 76.1% just by adding ZnO nanorods into the PVDF matrix without any mechanical or electrical treatment. A systematic investigation of PVDF‐ZnO nanocomposite films by using X‐ray diffractometer, Fourier transform infrared spectroscopy, and polarization‐electric field loop measurements supports the enhancement of β ‐phase in the flexible nanocomposite polymer films. The piezoelectric constant ( d 33 ) of the PVDF‐ZnO (15 wt%) film is found to be maximum of approximately −1.17 pC/N. Nanogenerators have been fabricated by using these nanocomposite films, and the piezoresponse of PVDF is found to enhance after ZnO loading. A maximum open‐circuit voltage 1.81 V and short‐circuit current of 0.57 μA are obtained for 15 wt% ZnO‐loaded PVDF nanocomposite film. The maximum instantaneous output power density is obtained as 0.21 μW/cm 2 with the load resistance of 7 MΩ, which makes it feasible for the use of energy harvesting that can be integrated to use for driving small‐scale electronic devices. This enhanced piezoresponse of the PVDF‐ZnO nanocomposite film‐based nanogenerators attributed to the enhancement of electroactive β ‐phase and enhanced d 33 value in PVDF with the addition of ZnO nanorods.